A tooth that could be saved - Osica, Piotr; Stelmach, Rafał; Janas-Naze, Anna (Journal of Education, Health and Sport, 2017)
<span style="font-size: 12.0pt; line-height: 115%; font-family: 'Times New Roman','serif'; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The article presents a case of a 25 year old woman who for economic reasons decided to remove a tooth 47, initially qualified for root canal treatment due to extensive inflammatory lesions. At one time, partially impacted tooth 48 was removed, which is the cause of chronic inflammation of this region.